Integrated Marketing Communication : An Exploratory Study Of Malaysian Advertising Agencies - Javasgi, Saeed (2009)
The study further extends knowledge on how advertising agency executives perceive IMC use and development in Malaysia. It provides a perspective on the current state of IMC and levels of implementation and usage in the marketing communications (marcom) landscape.